A Study of Guided Imagery Process: Awareness and the Discovery of Personal Meaning - Farr, Cally (Canadian Journal of Counselling and Psychotherapy, 2011)
This study describes the experiences of individuals using a specific guided imagery process designed to facilitate the generation of spontaneous imagery. The extent to which the procedure enhanced the subjects' discovery of meaning and awareness about their personal issues was examined. Five women participated in four guided imagery sessions held approximately one week apart. Data obtained by means of a post-session interview and the observations of the researcher were thematically interpreted. The descriptive analysis showed that the guided imagery process facilitated participants' discovery of personal meaning and increased understanding about their outer and inner lives. Subjects found the imagery enabled them to quickly discover and explore affective material related to important life experiences, issues, and relationships. It also allowed them to renew a connection with inner personal sources of creativity. Implications for counselling are discussed.